Rhabdomyolysis induced acute renal failure secondary to statins - Ram, R. (Medknow Publications & Media Pvt Ltd, 2013)
Rhabdomyolysis is a syndrome characterized by muscle necrosis and the release of intracellular muscle contents into the systemic circulation. We report a patient with chronic kidney disease who had deterioration of renal function due to combination of risk factors like hypothyroidism and interaction of amlodipine and clopidogrel with statins.